Regularización arquitectónica en asentamientos informales de vivienda en la localidad de bosa - Bogotá (2022)
For years, informal housing settlements have been a global urban problem; It should be noted that said problematic has a great presence in the countries of Latin America, because due to the disorder in the planning of the cities, the vulnerable population finds the opportunity to appropriate some land illegally and self-build on it to satisfy the basic needs of their families. Similarly, informal settlements have generated a habitat with characteristics of segregation and poverty; In addition, they present situations of irregularity, illegality and informality, by occupying spaces that are generally not urbanized or peripheral areas, in which they do not have access to basic services such as drinking water, sewage, electricity and gas natural.